The Rise and Essence Form of Contract for Evidentiary Purposes in the French Code civil and Its Effective Use on Polish Territories in the 19th and 20th Centuries - Dziadzio, Andrzej (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2026)
The article discusses the origins and significance of the French institution of the form of contract for evidentiary purposes in the context of the development of the principle of freedom of contract in canon law in Europe. The second aim of the paper is to demonstrate the implementation of this institution in the Polish legal system in the 19th and 20th centuries, as well as its application by Kraków courts following the introduction of the French Code civil on Polish soils.